Changes in Serum Total Protein, Albumin, C-Reactive Protein and High-Sensitivity C-Reactive Protein in Septicemic Patients in Enugu State University Teaching Hospital, Enugu, Nigeria - Ugwuene, Francis O; Ekeocha, Sandra N; Ezugwu, Domitilla I; Ogbodo, Sylvester O; Aniagolu, Miriam O; Ngwu, Martina A (British Journal of Healthcare and Medical Research, 2025)
Septicemia remains a major cause of morbidity and mortality in developing countries, particularly among children and immune-compromised individuals. The condition triggers complex inflammatory and biochemical alterations that can significantly affect serum proteins and acute-phase reactants. This study evaluated changes in serum total protein, albumin, C-reactive protein (CRP), and high-sensitivity C-reactive protein (hs-CRP) among septicemic patients attending Enugu State University Teaching Hospital (ESUTH). This was a cross-sectional study where fifty participants aged 1–16 years were enrolled, consisting of 25 confirmed septicemia patients with vital signs of temperature >38oC, respiratory rate >20 breaths per minutes, heart rate > 90 beats/min, WBC count > 12 X 109/L and 25 healthy controls. Serum total protein and albumin were determined by the biuret and bromocresol green methods, respectively. CRP and hs-CRP were analyzed using flouresence immunassay. Quality control sera were run alongside each batch of samples. Data were analyzed using one-way ANOVA and Student’s t-test with statistical significance at P < 0.05. The results revealed a marked decrease in total protein (59.38 ± 7.22 g/L) and albumin (28.84 ± 5.50 g/L) in the septicemic group compared with controls (67.74 ± 4.86 g/L and 44.60 ± 4.15 g/L, P < 0.05). Conversely, CRP was profoundly elevated (131.67 ± 42.82 mg/L verses 2.82 ± 0.83 mg/L, P < 0.05), while hs-CRP showed a non-significant increase (3.08 ± 0.78 mg/L verses 2.28 ± 0.35 mg/L, P > 0.05). sssssssssssThese findings indicated that hypoalbuminaemia and hyper-CRPemia are hallmarks of septicemia, reflecting an intense acute-phase response and hepatic protein redistribution. The insignificant change in hs-CRP may be due to assay sensitivity limits or late-phase sample collection. The study highlights CRP as a sensitive and reliable biomarker for early detection and monitoring of septicemia, while reduced serum protein and albumin levels may serve as prognostic indicators of disease severity.